Novel activating mutation of human calcium-sensing receptor in a family with autosomal dominant hypocalcaemia. (15th May 2015) - Baran, Natalia; ter Braak, Michael; Saffrich, Rainer; Woelfle, Joachim; Schmitz, Udo
Highlights: The novel activating mutation of Calcium Sensing Receptor (CaR) was described. In vitro studies on P136L-CaR with FURA-2/AM present a significantly left-shifted concentration-response curve for mutated receptor. MAPK-activity confirmed left-shifted activation curve of ERK, p38 and JNK for P136L-CaR compared with wild type CaR. The results confirm the association of biochemical and clinical features of the characterised family with the novel P136L-CaR mutation. The P136L-CaR mutation is responsible for ADH in this family. Abstract: Introduction: Autosomal dominant hypocalcaemia (ADH) is caused by activating mutations in the calcium sensing receptor gene ( CaR) and characterised by mostly asymptomatic mild to moderate hypocalcaemia with low, inappropriately serum concentration of PTH. Objective: The purpose of the present study was to biochemically and functionally characterise a novel mutation of CaR. Patients: A female proband presenting with hypocalcaemia was diagnosed to have "idiopathic hypoparathyroidism" at the age of 10 with a history of muscle pain and cramps. Further examinations demonstrated hypocalcaemia in nine additional family members, affecting three generations. Main outcome measure: P136L CaR mutation was predicted to cause gain of function of CaR . Results: Affected family members showed relevant hypocalcaemia (mean ± SD; 1.91 ± 0.1mmol/l). Patient history included mild seizures and recurrent nephrolithiasis. Genetic analysis confirmed that hypocalcaemia cosegregated with a heterozygous mutation at codon 136 (CCC → CTC/Pro → Leu) in exon 3 of CaR confirming the diagnosis of ADH. For in vitro studies P136L mutant CaR was generated by site-directed mutagenesis and examined in transiently transfected HEK293 cells. Extracellular calcium stimulation of transiently transfected HEK293 cells showed significantly increased intracellular Ca 2+ mobilisation and MAPK activity for mutant P136L CaR compared to wild type CaR. Conclusions: The present study gives insight about a novel activating mutation of CaR and confirms that the novel P136L-CaR mutation is responsible for ADH in this family.